(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
Abstract Historically, pesantren has a cultural institution was born by, from, for the society. Since its emergence in society, pesantren has a strategic role in developing community life. Though most pesantrens have positionized as education and religious institution (tafaqquh fiddin), but, in 1970’s there was a change in paradigm, where many pesantrens tried to do reposition on responding the dynamic social life. One of that reposition is a replacing pesantren as the agent of economic development. Pesantren Tiga Dimensi Foundation in Pangkep, South Sulawesi, is one of many pesantrens which do economic develompment, i.e. as agent of agrobussiness and maritime program centers. The initiative of this model come from the Regent of Pangkep, Baso Amirullah, not from pesantren community itself. Pesantren community were not involved in determining the culture of economic development in pesantren, but in this case, the bureaucracy were dominantly intervening to those programs. This condition caused the effectivity of economic development in pesantren run down.